The effect of globalization on energy consumption: Evidence from selected OECD countries - Ozcan, Burcu; Yucel, Ali Gokhan; Temiz, Mehmet (Elsevier, 2021)
The aim of this chapter is to analyze the relationship between globalization and energy consumption OECD countries. Such an investigation deserves attention in the modern era of globalization. To reach this purpose, we investigate the relationship between energy consumption, economic growth, urbanization, financial development, and globalization for 29 OECD countries spanning the period of 1971-2017. Due to cross-sectional dependence among the variables, we employed second generation panel unit root and cointegration tests. The findings show that there is a long-run relationship among energy consumption, economic growth, urbanization, globalization, and financial development. Empirical results reveal that economic growth, urbanization, financial development, and globalization are positively correlated with energy consumption. The study is concluded with important policy recommendations for OECD countries. © 2022 Elsevier Inc. All rights reserved.
Keywords: Cross-sectional dependence; Energy consumption; Globalization; OECD; Panel data analysis